A Holocene relative sea-level database for the Baltic Sea. (15th August 2021) - Rosentau, Alar; Klemann, Volker; Bennike, Ole; Steffen, Holger; Wehr, Jasmin; Latinović, Milena; Bagge, Meike; Ojala, Antti; Berglund, Mikael; Becher, Gustaf Peterson; Schoning, Kristian; Hansson, Anton; et al.
Abstract: We present a compilation and analysis of 1099 Holocene relative shore-level (RSL) indicators located around the Baltic Sea including 867 relative sea-level data points and 232 data points from the Ancylus Lake and the following transitional phase. The spatial distribution covers the Baltic Sea and near-coastal areas fairly well, but some gaps remain mainly in Sweden. RSL data follow the standardized HOLSEA format and, thus, are ready for spatially comprehensive applications in, e.g., glacial isostatic adjustment (GIA) modelling. We apply a SQL database system to store the nationally provided data sets in their individual form and to map the different input into the HOLSEA format as the information content of the individual data sets from the Baltic Sea area differs. About 80% of the RSL data is related to the last marine stage in Baltic Sea history after 8.5 ka BP (thousand years before present). These samples are grouped according to their dominant RSL tendencies into three clusters: regions with negative, positive and complex (transitional) RSL tendencies. Overall, regions with isostatic uplift driven negative tendencies dominate and show regression in the Baltic Sea basin during the last marine stage. Shifts from positive to negative tendencies in RSL data from transitional regions show a mid-Holocene highstand around 7.5–6.5 ka BP which is consistent with the end of the final melting of the Laurentide Ice Sheet. Comparisons of RSL data with GIA predictions including global ICE-5G and ICE-6G_C ice histories show good fit with RSL data from the regions with negative tendencies, whereas in the transitional areas in the eastern Baltic, predictions for the mid-Holocene clearly overestimate the RSL and fail to recover the mid-Holocene RSL highstand derived from the proxy reconstructions. These results motivate improvements of ice-sheet and Earth-structure models and show the potential and benefits of the new compilation for future studies. Highlights: A first standardized and publicly available Holocene relative sea-level database for the Baltic Sea is presented. The database holds 1099 revised data points with an estimation of vertical and chronological uncertainties. Negative RSL tendencies prevail over the positive and complex tendencies in the Baltic Sea Basin. Mid-Holocene RSL highstand occurred around 7.5–6.5 ka BP being consistent with the end of the final melting of the LIS. The contribution of ice loading in the eastern Baltic Sea Basin is likely overestimated in the ICE-5G and ICE-6G_C models.